Pluminasi as a New Composition Method in Contemporary Music | Pluminasi Sebagai Metode Komposisi Baru Pada Karya Musik Kontemporer - I Made Bayu Puser Bhumi; I Komang Sudirga; I Wayan Sudirana (GHURNITA: Jurnal Seni Karawitan, 2021)
The paradigm that was born from a mistake and misunderstanding of something different seemed to create a dividing barrier. Stigma has become a barrier between tradition and contemporary which is essentially related to one another. It takes a different perspective to find a correlation that will straighten out the "misunderstanding" of two things that are assumed to be different and often clashed. Pluminasi is a contemporary music based on the wealth or potential as well as traditional Balinese gamelan musical techniques. The exploration of musical potential in the form of sound wave manipulation with a resonator blockade system and the formation of the Ngorod musical formulation was realized using the creation method by Alma M. Hawkins, as well as the Manipulation composition method specially prepared for Pluminasi as a music composition. The application of this method resulted in three sound wave processing techniques and a musical formulation with a ngorod (swiping) system. As a contemporary musical composition, Pluminasi is worked on by exploring musical potentials and traditional gamelan playing techniques into a novelty where tradition is a strong foundation and not an attempt to destroy tradition.